Uma análise de aproximadores no Português Brasileiro na perspectiva da semântica formal - França, Mariana Nastri Perestrello de (Universidade Federal de São Carlos, 2018)
The phenomenon of vagueness has been studied for centuries and is detected, among other characteristics, for creating the Sorites paradox. Vagueness is identified when we face the lack of precise limits of terms (or their use), as for example, ‘careca’ (‘bald’): where is the delimitation for someone to be, or not, characterized as bald? Could it be the delimitation the quantity of hair on one’s head that makes us say that one person is bald? If it is the quantity of hair that delimits this characteristic, what happens when one single hair stranded is added to one’s head; is the person not bald anymore?, or what if one single hair strand is removed from one’s head; has the person become bald? It seems that simply counting hair strands is not the solutions to our problem and doesn’t suit our purpose. Another matter debated regarding vagueness is about its origin, some authors believe that its nature is epsitemic: the objectis in the world that we refer to are vague; others say that its nature is linguistic: the terms used to refer to things are vague. Assuming the linguistic nature of vagueness as a problem on the terms or on use of the terms, Sauerland and Stateva (2011) elaborate a hypothesis to interpret this phenomenon, identifying two types of vagueness: (i) epistemic and (ii) scalar. As an argument in favor of this idea the authors propose the linguistic category of approximators: lexical items or construction that modify vague predicates making them more or less precise. Following this hypothesis, the approximators can be divided between two classes according to their compatibility with one of the two proposed types of vagueness. In this dissertation we aim to describe some approximators in Brazilian Portuguese (BP), and verify the duality of phenomenon in analysis, contributing to the description of (BP) and the comprehension of vagueness. In order to do so we delimit the vagueness phenomenon from the linguistic point of view separating it from other natural language phenomena; we then introduce a precise definition of vagueness and approximators and a method to investigate the linguistics mechanisms of the vague predicates, proposing a semantic and pragmatic description of some BP approximators.
An analysis of approximators in Brazilian Portuguese in the perspective of formal semantics
Keywords: Vagueza; Aproximadores; Vagueza epistêmica; Vagueza escalar; Semântica formal; Vagueness; Aproximators; Epistemic vagueness; Scalar vagueness; Formal semantics; LINGUISTICA, LETRAS E ARTES::LINGUISTICA